Current knowledge and practice of Australian and New Zealand health‐care professionals in sarcopenia diagnosis and treatment: Time to move forward!. (15th October 2019) - Yeung, Suey S. Y.; Reijnierse, Esmee M.; Trappenburg, Marijke C.; Meskers, Carel G. M.; Maier, Andrea B.
Abstract: Objectives: To describe the current knowledge and practice of sarcopenia diagnosis and treatment among health‐care professionals before, directly after and 6 months after a professional development event on sarcopenia. Methods: This longitudinal study included Australian and New Zealand health‐care professionals who completed questionnaires on knowledge, practice and barriers regarding sarcopenia before, directly after and 6 months after attending a professional development event on sarcopenia. Results: A total of 250 professionals participated; 84 completed the 6‐month questionnaires. Before, directly after and at 6 months, respectively, 14.7%, 93.4% and 59.5% identified sarcopenia as a disease; 2.0%, 79.6% and 38.1% correctly answered the sex‐specific cut‐offs for low handgrip strength. Respectively, 12.0% and 14.3% reported to make sarcopenia diagnoses as part of their practice before and at 6 months. Conclusions: Knowledge about sarcopenia is limited among health‐care professionals who attended a professional development event. Retention of knowledge remains a challenge to be addressed.